Scar Endometriosis: Case Report with Literature Review - Gupta, P; Gupta, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Endometriosis is defined as presence of functioning endometrial tissue outside the uterine cavity. Endometriosis can sometimes occur in a previous surgical scar. Scar endometriosis is rare and difficult to diagnose. It mostly follows obstetrical and gynecological surgeries. This condition is often confused with other surgical conditions. We are reporting one case of scar endometriosis involving rectus sheath following cesarean section. The patient required wide surgical excision of the lesion. The pathogenesis, diagnosis and treatment of this rare condition are being discussed. DOI: http://dx.doi.org/10.3126/njog.v9i2.11764